Rwanda : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waivers of Nonobservance of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Sixth Review under the Poverty Reduction and Growth Facility (PRGF) for Rwanda. All end-2008 quantitative performance criteria were met, and performance through March 2009 was broadly satisfactory. IMF staff recommends completion of the sixth review under the PRGF arrangement based on Rwanda's performance and understandings reached on the macroeconomic program for 2009/10. IMF staff also supports the authorities' request for waivers of nonobservance of performance criteria on nonconcessional borrowing and nonintroduction of multiple currency practices.